ANALISA SEMIOTIKA FERDINAND DE SAUSSURE TERHADAP LIRIK LAGU “SAKURA NO HANABIRATACHI” KARYA JKT48 - Fahmi Handiansyah, Muhammad Rizki Fadhillah, Calvin Eka Sambora, Zaky Aulia Drajat, Riza Fahlapi (ADISAM PUBLISHER, 2024)
This study aims to interpret the meaning of farewell contained in the lyrics of the song